Hubungan Self Efficacy dan Coping Stres terhadap Performa Kerja pada Karyawan Outsouching PT. X di Sidoarjo - Farhan Aditya Pratama; Eko Hardi Ansyah (IPM2KPE, 2024)
This research aims to 1) evaluate the relationship between self-efficacy and outsourced employee performance, 2) analyze the relationship between stress coping and outsourced employee performance, and 3) examine the joint relationship between self-efficacy and stress coping on outsourced employee performance. This research uses a quantitative approach with a correlational type of research. Data was collected through self-efficacy questionnaires (24 questions), stress coping (25 questions), and work performance (28 questions). The results of the research show that 1) there is a positive relationship between self-efficacy and outsourced employee performance, 2) there is no relationship between stress coping and outsourced employee performance, and 3) there is no significant relationship between self-efficacy and stress coping together on outsourced employee performance. Conclusions, demonstrate the complexity of factors influencing the performance of outsourced employees and provide a basis for further research. Keywords: Coping Stress, Work Performance, Self Efficacy